Limberg’s flap technique: a defect repair method for ear lobe reconstruction in recurrent earlobe keloids: a case report - Tantry, Deepalakshmi; Tantry, Gururaj; R. S., Chitra; M., Sapna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
The article acts to focus and aid in the localization of sound. Its shape is aesthetically important as it shows considerable inter-individual variability which reflects its multicomponent and is quite challenging for the surgeons during the planning of reconstruction as it is complex and equally important. It’s complex undulating structure and topography includes fibro elastic cartilage, perichondrium and the skin. The ear lobule is an important reference point for symmetry of the face and its loss causes an obvious aesthetic abnormality. Excessive healing can be as significant as delayed or non-healing. Recurrent earlobe keloids are among the most challenging conditions and may have significant psycho-social impact for the patient. Their aesthetic considerations are serious and despite a variety of treatment options, they often proved to be recurrent. It is likely that more operative interventions are required for excessive healing. Type II A defects are characterized by loss of the ear lobule without presence of a nubbin of tissue attached to the cheek. The goal of surgery should be an aesthetically pleasing reconstruction that maintains symmetry with the opposite ear lobule. The Limberg‑flap technique using a doubled‑over skin flap allows a one stage reconstruction of the ear lobule. The aesthetic results are generally well acceptable and hence here we present a case where we combine this technique with the excision for better results of long-term refractory cases.